Genetic composition of green sea turtles (Chelonia mydas) at coastal feeding areas of Uruguay - Prosdocimi, Laura; Vilaca, Sibelle Torres; Naro-Maciel, Eugenia; Caraccio, Maria N.; Formia, Angela; Vélez-Rubio, Gabriela M. (Frontiers in Amphibian and Reptile Science, 2024)
This study investigated the genetic composition of green sea turtles (Chelonia mydas) foraging in coastal waters of Uruguay (ca. 33º-35º S) in the Southwestern Atlantic Ocean. The region is utilized by five of the seven extant marine turtle species, with the green turtle being the most abundant in coastal habitats. In total 201 tissue samples were collected from turtles that had stranded or were intentionally captured for scientific research along the Uruguayan coast during two sampling periods (2003-2005 and 2009-2014). There was no significant difference between or within collection intervals or sites, and thus samples were pooled for analysis. Overall, 12 mitochondrial control region haplotypes ( 481 bp) and 10 subhaplotypes ( 780 bp) were identified, all of which had been previously detected at Atlantic or Caribbean nesting beaches. Mixed Stock Analysis revealed that most turtles traced to the Ascension Island rookery, representing a substantial connection to the remote mid-Atlantic island thousands of kilometers distant. Other nesting areas, such as Guinea Bissau in Africa and Trindade Island in Brazil represented less significant sources. Although geographic distance from the nesting beach is unlikely to predict source contributions to this juvenile developmental feeding ground, rookery population size and ocean current influences could not be discounted. The lack of significant temporal or spatial genetic structure within Uruguayan waters suggests that the turtles disperse along this part of the coast, but the differentiation from most other feeding grounds supports the distinctiveness of this aggregation. These findings have important implications for conservation, supporting the maintenance of existing protected areas as well as the creation of new ones along with legislative enforcement, as the Uruguayan coast supports a unique mixed stock of green turtles connected to various nesting colonies and feeding grounds. These results underscore the need for protected areas and management measures that encompass habitats where these endangered species occur, with the aim of ensuring their long-term conservation.